Evaluasi Dampak Koagulan Alami dalam Menurunkan Konsentrasi Pewarna dalam Limbah Industri: Penelitian Meta-Analisis - Annisa Kharismaningtyas Astuti (Universitas Widya Gama Mahakam Samarinda, 2023)
Disposal of coloured liquid waste into the environment can profoundly impact and harm the environment if released without proper handling. There are various treatment technologies to remove dyes, one of which is the wastewater coagulation method which is often used because of its efficiency and relatively low capital costs. Many coagulants are used in wastewater treatment processes, including natural coagulants. This study purposed to analyze the effectiveness of natural coagulants in decreasing the level of dyes in industrial wastewater using the meta-analysis method. Data from ten studies conducted between 2012 and 2022 were compiled from databases like Google Scholar, Portal Garuda, Semantic Scholar, and Scopus. A meta-analysis method was used to analyze the data. The meta-analysis revealed significant findings. The mean difference for each variable resulted in a p-value of 0.001 or p <0.05 for each variable, indicating a substantial impact on reducing dye concentrations. Specifically, the dose of natural coagulant, pH, stirring time, and stirring speed were found to be significant factors. The use of natural coagulants in wastewater treatment processes has a considerable effect on reducing dye levels, as evidenced by the significant p-values for the variables studied.